A simple model to study wave-surge interaction - MUKHOPADHYAY, P.S.; MANDAL, G. K.; SEN, G. K.; SINHA, D. K. (MAUSAM, 1997)
ABSTRACT. In this paper we have tried to set up a mathematical model that will show the contribution of wind-induced surface waves of the ocean, on surges in shallow basin of Bay of Bengal. For this, the energy balance equation, excluding non-linear forcing term, is considered and solved by Lax-Wendroff integration scheme. Wind is specified over all the grid points following Cardone' s formulation. The hydrodynamic equations in linearised form as used by Jelesnianski have been considered and using Shuman's algorithm, those equations have been solved. In the process of solving these equations, the output of the energy balance equation is included as wave set up term to incorporate energy contribution of wind waves to surges. The estimated surge height is compared with and without considering wave contribution.